Intolerance of uncertainty, fear of contamination and perceived social support as predictors of psychological distress in NHS healthcare workers during the COVID-19 pandemic. Issue 2 (7th February 2023) - Beck, Emily; Daniels, Jo
ABSTRACT: Psychological distress has been repeatedly quantified over the course of the pandemic, however this has not always included broader healthcare workers, and has mostly focused on prevalence and occupational factors. This study investigated intolerance of uncertainty (IOU), fear of contamination and perceived social support as key predictors of psychological distress in healthcare professionals, between the 10 th and 23 June 2020, during the first wave of the COVID-19 pandemic. This study was a cross-sectional, online survey design. Opportunity sampling was used to recruit to the study, primarily using social media sites and snowballing techniques. The final sample included 342 National Health Service (NHS) healthcare workers. IU ( p < .001), gender ( p < .001), fear of contamination ( p = .007), perceived social support ( p = .012), and age ( p = .017) significantly predicted psychological distress in the sample and accounted for 36.2% of variance in psychological distress scores. IOU accounted for 28.2% of this variance. A two-way post hoc ANOVA, looking at gender and profession, showed a significant main effect of gender on psychological distress scores ( F (1, 218) = 7.156, p = .008, ηp 2 = .032), with females reporting significantly higher psychological distress scores compared to males. In conclusion, higher levels of intolerance of uncertainty, fear of contamination and lower levels of perceived social support significantly influenced higher scores of psychological distress. These factors should be considered when adapting and delivering evidence-based interventions to healthcare staff during this crisis.